P188 Middle small-bowel segment Lewis score may predict long-term outcomes among patients with quiescent Crohn's disease. (30th January 2023) - Ukashi, O; Yablecovitch, D; Lahat, A; Selinger, L; Neuman, S; Eliakim, R; Ben-Horin, S; Kopylov, U
Abstract: Background: Video capsule endoscopy (VCE) has been proven to accurately diagnose small-bowel inflammation and predict flares among patients with quiescent Crohn's disease (CD). In this study we aimed to predict worse clinical outcomes over an extended follow-up. Methods: This was a post-hoc analysis of adult patients with quiescent small-bowel CD who were followed with VCE, inflammatory biomarkers and magnetic resonance enterography (MRE) in a prospective study (between 2013-2018). We extracted extended clinical data from our hospital electronic health records to include the most recent follow-up (until Apr 2022). The primary composite outcome was clinical exacerbation defined as either intestinal-surgery, endoscopic dilation, CD-related admission, need for corticosteroids or biological/immunomodulator treatment change during the follow-up. Results: Out of the 61 patients who were included in the study (median age of 29 [24-37] years, male–57.4%, current biologic treatment–46.7%), 18 patients met the composite outcome during an extended long-term follow-up (median of 58 [interquartile range 35-93] months). On univariable analysis, complicated (Hazard ratio [HR] 7.348, p=0.002) and stricturing disease-phenotype (HR 5.305, p=0.001) were associated with higher risk for clinical exacerbation during follow-up. A baseline VCE middle small-bowel segment Lewis score (midLS) of≥135 identified patients with future exacerbation (AUC of 0.767, 95% CI 0.633-0.902, p=0.001, HR 6.317, negative predictive value [NPV] of 93%), while the conventional Lewis score had an AUC of 0.734 (CI 0.589-0.879, p=0.004). Performing sensitivity analysis restricted to patients with either complicated (n=34) or stricturing disease-phenotype (n=26), we revealed that midLS still predicted disease exacerbation during the extended follow-up (AUC of 0.747 and 0.753, respectively) in these patients. Conclusion: MidLS predicts treatment failure in quiescent Crohn's disease patients (median follow-up 5 years) independently of disease-phenotype.